2016
DOI: 10.1016/j.cirp.2016.04.087
|View full text |Cite
|
Sign up to set email alerts
|

Impact reduction potential by usage anticipation under comfort trade-off conditions

Abstract: Este documento contiene información de prueba. Contáctese con el administrador del Centro para el acceso al documento originar del registro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…24h) predictions are straightforward with the unsupervised approach as it suces to identify the current prole. A wide variety of applications can benet from intelligent control systems, like the one presented in this paper, which can be illustrated by the framework developed in [11] that identies the reduction potential of any application by intelligent control.…”
Section: Methods and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…24h) predictions are straightforward with the unsupervised approach as it suces to identify the current prole. A wide variety of applications can benet from intelligent control systems, like the one presented in this paper, which can be illustrated by the framework developed in [11] that identies the reduction potential of any application by intelligent control.…”
Section: Methods and Applicationsmentioning
confidence: 99%
“…The threshold should therefore be set in an appropriate manner which is typically case specic. For example, in previous work [11], a user tolerance parameter U T was dened, binarising the user prole by discarding, i.e. setting to zero, U T % of the area under the curve with the lowest probabilities and elevating the remaining probabilities to 1.…”
Section: Predictive Performance Analysismentioning
confidence: 99%
“…A methodology to determine the reduction potential by intelligent control of any given application was developed by Duflou et al (2016), as part of the PERPETUAL project [169]. The authors identified the following selection of system and usage features that influence the reduction potential [ where ∆ 8/./, represents the difference between 8/./, and 8/.1=AB , 8/./, the duration of a transition from standby to a certain state (e.g.…”
Section: Intelligent Systemsmentioning
confidence: 99%